AN ANALYSIS OF TEACHERS’ PERCEPTION ON THE USE OF AUTHENTIC ENGLISH READING MATERIALS OF VIA ENGLISH COURSE - Nina Afriani; Samsul Amri; Edi Ardian (Program Studi Pendidikan Bahasa Inggris, 2022)
This study aims to determine the teacher's perception of the Via English Course about authentic materials that can be taken from the internet, magazines, and newspapers and so on. This type of research is descriptive quantitative. The population of this study are teachers at the Via English Course for the 2021/2022 academic year. The number of population and samples from this study were 11 people taken using total sampling technique. To find out the teacher's perception of using authentic materials in reading skills. Researchers collected data that is quantitative data. For data analysis, the researcher used observational analysis and a questionnaire to determined the final result of the teacher's perception in using authentic material in reading skills. The results of the test show that the teacher's perception of using authentic material in Via English Course Tembilahan is categorized with an average of 88.9% (Very Good). The researcher concluded that the teacher's perception of using authentic material in the Tembilahan English Course was very good because by using authentic material students were more active and more enthusiastic in reading English.